2022
DOI: 10.3390/ijerph192416774
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Profiles of Electronic Nicotine Delivery System (ENDS) Aerosols Reflect Both the Chemical Composition and the Numbers of E-Liquid Ingredients–Focus on the In Vitro Toxicity of Strawberry and Vanilla Flavors

Abstract: Propylene glycol (PG) and glycerin (G) are the most widely used humectants in electronic nicotine delivery system (ENDS) devices. Carbonyls are present in aerosols produced when ENDS devices heat PG and G. Whether aerosolized PG and G are innocuous to the lungs has not been established. Here, we determined the chemical profiles of ENDS aerosols containing three humectant ratios (30/70, 50/50 and 70/30, PG/VG), for three flavors (strawberry, vanilla and Catalan cream) containing either 12 or 18 mg/mL of nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We conducted real-time and offline characterization of the e-cig aerosols via a MicroDustPro (Casella) and traditional gravimetric sampling methods, respectively, as previously described [ 22 , 28 ]. The chemical analysis of the vanilla-flavored e-cig aerosol produced under the same conditions as those in this study was published by our research group elsewhere [ 33 ] and revealed that this vanilla-flavored e-cig aerosol contained high concentrations of PG and G (>2 mg/puff) in addition to having elevated levels of butyraldehyde (>1 µg/puff).…”
Section: Methodsmentioning
confidence: 54%
“…We conducted real-time and offline characterization of the e-cig aerosols via a MicroDustPro (Casella) and traditional gravimetric sampling methods, respectively, as previously described [ 22 , 28 ]. The chemical analysis of the vanilla-flavored e-cig aerosol produced under the same conditions as those in this study was published by our research group elsewhere [ 33 ] and revealed that this vanilla-flavored e-cig aerosol contained high concentrations of PG and G (>2 mg/puff) in addition to having elevated levels of butyraldehyde (>1 µg/puff).…”
Section: Methodsmentioning
confidence: 54%
“…On the grounds of these observations, it is evident that this approach is based on the worst toxicological conditions, with the highest risks for users. A similar approach can be found in many articles using these worst risk exposure conditions in studying the effects of EC emissions on cell cultures 4 6 and on laboratory animals 7 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Another e-liquid component linked to e-cigarette toxicity is flavoring agents (Herbert et al, 2023;Noël and Ghosh, 2022;Shen et al, 2016). In their analysis of e-liquid cytotoxicity on human MG-63 and Saos-2 osteoblast-like cells, (Otero et al, 2019) reported a decrease in cell viability, suggesting a toxic effect independent of the presence of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…PG and VG are humectants that mimic cigarette smoke and transport nicotine during vaping. While VG provides visual smoke and improves taste and smell, PG is associated with health issues such as sore throat, headache, and dizziness (Harvanko et al, 2019;Guo et al, 2022;Noël and Ghosh, 2022). These main e-liquid constituents have been generally considered to be safe ingredients for oral ingestion (FDA, 1980).…”
Section: Introductionmentioning
confidence: 99%